PENURUNAN BOD, TSS DAN TOTAL N MENGGUNAKAN MIKROORGANISME INDIGEN LIMBAH CAIR TAHU DENGAN PROSES MBBR - Dewa Gede Arya Sekar Laksana Dewa; Yayok Suryo Purnomo (EnviroUS, 2021)
Tofu industry is a business that is established in the context of developing activities in the food sector have a negative impact is in the form of waste which causes pollution problems so that it can damage the environment. One of the biological treatments that can be used is the Moving Bed Biofilm Reactor (MBBR) process by utilizing independent microorganisms in tofu liquid waste. The MBBR process is principally an activated sludge process which is enhanced by the addition of moving media and aeration to the reactor. This study aims to determine the performance of MBBR in reducing the content of BOD, TSS and Total N in tofu wastewater. the media used is spoon media. variations of air flow used are 3, 3.5, 6, 7 and 9 L / min. The next variation is the sampling time starting from 0, 6, 8, 12 and 16 hours. The results of this study indicate that the optimum ability of MBBR and indigenized microorganisms is the variation of air flow rate of 3.5 L / min at 16 hours of sampling time. the MBBR reactor was able to reduce BOD by 85%, TSS by 91% and Total N by 83.2%. Keywords: Moving Bed Biofilm Reactor (MBBR), Tofu Wastewater